2018
DOI: 10.1016/j.aninu.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation of Brachiaria brizantha cv. Piatá and Napier grass with Desmodium distortum on feed intake, digesta kinetics and milk production in crossbred dairy cows

Abstract: This study was planned to analyse the basis that make Brachiaria species with greater feeding value than Napier grass (Pennisetum purpureum) for lactating dairy cows. Forty lactating crossbred cows were stall-fed on Brachiariabrizantha cv. Piatá or Napier grass cv. French Cameroon supplemented (mixed on fresh matter basis) or unsupplemented with Desmodium distortum, a forage legume. All cows were fed on fresh matter basis under small-holder farming conditions. Results showed that B. brizantha cv. Piatá had hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In this study, the improved grasses had the highest nutrient digestibility, with BhH superior to NGH. In line with this, Mutimura et al [ 14 ] reported that, on the basis of palatability, Brachiaria is preferred to Napier grass. In our current study, NDF digestibility increased from NPH (48.1%) to BhH (56.5%) in TMR diets.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In this study, the improved grasses had the highest nutrient digestibility, with BhH superior to NGH. In line with this, Mutimura et al [ 14 ] reported that, on the basis of palatability, Brachiaria is preferred to Napier grass. In our current study, NDF digestibility increased from NPH (48.1%) to BhH (56.5%) in TMR diets.…”
Section: Discussionmentioning
confidence: 71%
“…Dry matter intake increased as dietary CP content increased because of the inclusion of TTS, NGH, or BhH as nitrogen sources in a basal diet. Similarly, Mutimura et al [ 14 ] reported that the differences in DMIs of Napier grass and Brachiari brizantha fed as sole diets are related to the dietary composition of grasses. In this study, the improved grasses had the highest nutrient digestibility, with BhH superior to NGH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2013, eight improved Brachiaria cultivars were introduced and evaluated for adaptation and biomass yield in different agro-ecological zones (Ghimire et al 2015). These cultivars were successfully integrated into mixed crop-livestock system that subsequently improved forage availability and livestock productivity (Mutimura et al 2016;Mutimura et al 2018).…”
Section: Introductionmentioning
confidence: 99%